In situ preparation and determination of electrochemical and electrochromic properties of copper phthalocyanine-polyaniline nanocomposite films. Issue 59 (25th October 2019) - Ouyang, Mi; Hu, Xuming; Shao, Xiongchao; Chen, Lu; Li, Weijun; Bai, Ru; Zhang, Ling; Lv, Xiaojing; Tameev, Alexey; Zhang, Cheng
Abstract : A CuPc-PANI composite film with good electrochromic properties and obvious pseudocapacitance performance was successfully prepared using in situ electrochemical methods. Abstract : Copper phthalocyanine (CuPc) films with different morphologies were electrodeposited on the surfaces of ITO electrodes. Then, in each case, a polyaniline (PANI) film was electrochemically polymerized in situ on the surface of the copper phthalocyanine film to form a CuPc-PANI composite film. The electrochemical properties of the CuPc-PANI composite film were observed to be much better than those of the film without CuPc. With the modification involving the CuPc nanowires, the composite film formed a finer particle surface and an increased interface area between the PANI and the electrolyte. Compared to the single-component PANI film, the CuPc-PANI composite film exhibited better performance with a higher optical contrast (58% at 730 nm), a faster response speed (coloring time of 1.02 s, discoloring time of 1.96 s), and better cycling stability (68.71% of the initial electrochemical activity after 500 cycles, in contrast to only about 48.02% for PANI). Moreover, the CuPc-PANI film shows a new feature that can be used as a supercapacitor (specifically a capacitance value of about 5.4 mF cm −2 at typical currents). Our results demonstrate that the prepared CuPc-PANI composite film is one of the best candidates for multiple potential applications such as high-performance polymer electrochromic materials and supercapacitors.